2017
DOI: 10.1161/circulationaha.117.027983
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlation of SCN5A Mutation for the Clinical and Electrocardiographic Characteristics of Probands With Brugada Syndrome

Abstract: Brugada syndrome patients with mutations exhibit more conduction abnormalities on ECG and have higher risk for cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
133
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 48 publications
2
133
3
1
Order By: Relevance
“…Subsequently, the 45 remaining articles were reviewed for further details, and 28 studies did not meet the inclusion criteria. Finally, 17 studies involving 1780 BrS probands were included in this meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, the 45 remaining articles were reviewed for further details, and 28 studies did not meet the inclusion criteria. Finally, 17 studies involving 1780 BrS probands were included in this meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…In total, seven studies (four involving Asians, two involving Caucasians and one involving multiple ethnicities) examined the association between the SCN5A mutation status and MAEs during follow up. As shown in Figure , the SCN5A mutation status was associated with an increased risk of MAEs in all BrS patients (OR = 1.78, 95% CI 1.19‐2.26; P = .005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dr. Yamagata (National Cerebral and Cardiovascular Center) reported that probands with Brugada syndrome (BrS) and SCN5A mutations had more conduction abnormalities on ECG, and exhibited a higher risk for cardiac events. 11 In the Late Breaking Cohort Studies 4, environmental factors of atrial fibrillation (AF) and treatment were discussed. Dr. Okumura (Hirosaki University) et al combined the data of 5 major AF registries in Japan and estimated significant risk factors for ischemic stroke in non-valvular AF patients.…”
Section: Management Of Arrhythmia: Basic and Clinical Point Of Viewsmentioning
confidence: 99%